Unleashing the Power of the Global Web - Singh, Nitish (Language at Work - Bridging Theory and Practice, 2009)
Today's economy is characterized by increased connectivity of global markets, resource mobility, shifts in global production, unfettered global competition and turbo charging of emerging economies like China, India and Brazil. To thrive in this volatile and dynamic global economy people need high-end knowledge skills which can prepare them to respond to these changes in a global economy. One way to envision and then acquire skills for the future marketplace is to understand the emerging global megatrends.